The Relation Between Walking and Language in Infant Siblings of Children With Autism Spectrum Disorder. Issue 3 (23rd October 2017) - West, Kelsey L.; Leezenbaum, Nina B.; Northrup, Jessie B.; Iverson, Jana M.
Abstract : In typical development, walk onset is accompanied by increased language growth (e.g., Walle & Campos, 2014). The present study explored whether this relation may be disrupted in the infant siblings of children with autism spectrum disorder (ASD; heightened risk of receiving an ASD diagnosis; HR), a population exhibiting substantial variability in motor and language development (e.g., Gamliel, Yirmiya, & Sigman, 2007; Landa & Garrett‐Mayer, 2006). Receptive and expressive language were examined across the transition to walking in three groups of HR infants (no diagnosis, language delay, and ASD; N = 91, 8–18 months) and in infants with no family history of ASD ( N = 25; 9–15 months). Only infants with an eventual ASD diagnosis did not show increased language growth following walk onset.